2018
DOI: 10.3390/app8122588
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Generation in MHD Eyring–Powell Fluid Flow over an Unsteady Oscillatory Porous Stretching Surface under the Impact of Thermal Radiation and Heat Source/Sink

Abstract: In this article, we have briefly examined the entropy generation in magnetohydrodynamic (MHD) Eyring-Powell fluid over an unsteady oscillating porous stretching sheet. The impact of thermal radiation and heat source/sink are taken in this investigation. The impact of embedded parameters on velocity function, temperature function, entropy generation rate, and Bejan number are deliberated through graphs, and discussed as well. By studying the entropy generation in magnetohydrodynamic Eyring-Powell fluid over an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 40 publications
1
44
0
Order By: Relevance
“…For a solution of the modeled Equations (13)-(15) with boundary conditions (16) are solved with the homotopy analysis method (HAM) [44][45][46][47][48][49][50]. HAM is used due to its outstanding outcomes.…”
Section: Solution Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…For a solution of the modeled Equations (13)-(15) with boundary conditions (16) are solved with the homotopy analysis method (HAM) [44][45][46][47][48][49][50]. HAM is used due to its outstanding outcomes.…”
Section: Solution Proceduresmentioning
confidence: 99%
“…The other relevant studies can be seen in [37][38][39][40]. The most recent study on nanofluids and nanotubes with thermal conductivity can be seen in [41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Muhammad and Khan 21 also used entropy generation analysis to study the influence of radiation and second‐order slip effects on magnetohydrodynamics (MHD) viscous flow through a curved surface in the presence of nanoparticles. Some of the recent studies on the irreversibility analysis can also be found in Refs 22–31 …”
Section: Introductionmentioning
confidence: 99%
“…Jawad et al [58] studied 3-D single-wall carbon nanotubes rotating flow with the impact of nonlinear thermal radiation and viscous dissipation in the presence of aqueous suspensions. Other related work can be seen in [59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%